Vertical farming product verrtarrow / Muhammad Faiz Abu Hassan - Abu Hassan, Muhammad Faiz (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Introducing Vertarrow products, a unique solution designed to fill the space in the balcony area of your home. The newly developed equipment is a vertical plant system that has a compact and user-friendly quality. The design aims to attract users and attract users to plant trees in their balcony area. In addition, this product aims to make it easier for users to plant trees if they do not have space to cultivate. It provides a sustainable and efficient way to grow fresh herbs and vegetables at home, and it also has free space to store plant items. This product is released in 3 different color versions, with this the buyer can choose the color they like. This product also has a water container at each level and this product is also easy to install and use.